Mental illness is associated with more pain and worse functional outcomes after ankle fracture. Issue 2 (June 2019) - Simske, Natasha M.; Audet, Megan A.; Kim, Chang-Yeon; Benedick, Alex; Vallier, Heather A.
Abstract: Objectives: To assess clinical and functional outcomes after ankle fracture in patients with preexisting mental illness. Design: Retrospective study. Setting: Level 1 trauma center. Patients/Participants: One thousand three hundred seventy-eight adult patients treated for ankle fractures; 228 (17%) had preexisting mental illness. Intervention: Open reduction internal fixation. Main outcome measure: Rates of complications and reoperations. Functional outcomes were assessed via Foot Function Index (n = 530) and Short Musculoskeletal Function Assessment (n = 530). Results: Depression was the most common mental illness (63%), followed by anxiety (23%). Mental illness was associated with older age, female sex, and preexisting medical comorbidities, including diabetes and obesity. Mental illness was not associated with specific fracture patterns or open injury. Complications occurred no more often in patients with mental illness, but secondary operations (13% vs 7%) were more likely, particularly implant removals (8% vs 4%), both P  < .05. Functional outcomes were worse in mentally ill patients as measured by the Foot Function Index (39 vs 30, P  = .006) and Short Musculoskeletal Function Assessment Mobility: 45 vs 35, Bothersome: 35 vs 26 and Dysfunction: 35 vs 26, all P  < .01. Conclusion: Secondary operations were nearly 50% more frequent in patients with mental illness, and functional outcome scores were significantly worse, suggesting that mental illness, unrelated to injury and treatment parameters, has major influence on outcomes. In the future, strategies to identify and treat mental illness prior to and after treatment could improve functional outcomes following ankle fracture. Abstract : Supplemental Digital Content is available in the text